"To a Poet a Thousand Years Hence", de James Elroy Flecker. - Siles Artés, J. (Didáctica. Lengua y Literatura, 1999)
The poet expresses content witb some of bis cultural values and sends a salutation to another poet a thousand years bence.
Keywords: Musie; lave; prayers; pod; through time and space